2015
DOI: 10.1039/c5tb00879d
|View full text |Cite
|
Sign up to set email alerts
|

Shaping bio-inspired nanotechnologies to target thrombosis for dual optical-magnetic resonance imaging

Abstract: Arterial and venous thrombosis are among the most common causes of death and hospitalization worldwide. Nanotechnology approaches hold great promise for molecular imaging and diagnosis as well as tissue-targeted delivery of therapeutics. In this study, we developed and investigated bioengineered nanoprobes for identifying thrombus formation; the design parameters of nanoparticle shape and surface chemistry, i.e. incorporation of fibrin-binding peptides CREKA and GPRPP, were investigated. Two nanoparticle platf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 53 publications
0
88
0
Order By: Relevance
“…The lower adhesion of AR9 rods compared to AR4 rods, despite their higher contact surface area, is likely due to their entrapment in the capillaries as AR9 rods have a major axis length of roughly 9 μm [15]. Recently, Wen et al have also demonstrated that rod-shaped particles (elongated TMV) functionalized with binding peptides and contrast agents (gadolinium) could be targeted to activated platelets/thrombus in mouse carotid artery at a higher magnitude compared to sphere-like particles (icosahedral cowpea mosaic virus) [89].…”
Section: Vascular Wall Margination and Attachmentmentioning
confidence: 97%
“…The lower adhesion of AR9 rods compared to AR4 rods, despite their higher contact surface area, is likely due to their entrapment in the capillaries as AR9 rods have a major axis length of roughly 9 μm [15]. Recently, Wen et al have also demonstrated that rod-shaped particles (elongated TMV) functionalized with binding peptides and contrast agents (gadolinium) could be targeted to activated platelets/thrombus in mouse carotid artery at a higher magnitude compared to sphere-like particles (icosahedral cowpea mosaic virus) [89].…”
Section: Vascular Wall Margination and Attachmentmentioning
confidence: 97%
“…147 Some other advantageous properties that are conferred by elongated particles include better margination toward the vessel wall and stronger adherence due to greater surface area for interaction, which not only have implications for tumor homing but also for enhanced targeting of cardiovascular disease. 148, 149 …”
Section: Applications Of Virus-based Particlesmentioning
confidence: 99%
“…The majority of studies focus on cardiovascular and cancer detection. Although other supramolecular nanoparticles such as liposomes, viral capsids, and nanoemulsions incorporate peptide conjugates, peptides are often added after self-assembly of the particle, and we refer the reader to other recent articles and reviews [141144]. …”
Section: Conjugate-conjugate Interaction Driven Self-assemblymentioning
confidence: 99%